2022
DOI: 10.1039/d2qi00715k
|View full text |Cite
|
Sign up to set email alerts
|

Cyanamide-defect-induced built-in electric field in crystalline carbon nitride for enhanced visible to near-infrared light photocatalytic activity

Abstract: Carbon nitride materials have achieved high accomplishments in solar to hydrogen energy conversion under visible light. However, the weak kinetics and rapid recombination of photogenerated charge carriers result in a...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…To further verify the improvement of charge separation by ferroelectric polarization, Kelvin probe force microscopy (KPFM) was employed to identify the surface potential of the samples. 27,28 The images of the surface potential distribution of b-BaTiO 3 ( p) and b-BaTiO 3 nanoparticles in the dark and under 400 nm light irradiation are shown in Fig. 3d, e and g, h, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…To further verify the improvement of charge separation by ferroelectric polarization, Kelvin probe force microscopy (KPFM) was employed to identify the surface potential of the samples. 27,28 The images of the surface potential distribution of b-BaTiO 3 ( p) and b-BaTiO 3 nanoparticles in the dark and under 400 nm light irradiation are shown in Fig. 3d, e and g, h, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…By strengthening the intensity of internal electric field, enlarging the scope of internal electric field and building multiple internal electric fields, the photocatalytic activities were further improved. As shown in Figure 14, elemental doping, [103,147] defect engineering, [10,32] molecular regulation, [148] facet and crystallinity control can be used to heighten the intensity of internal electric field, [117,118] and strengthening the applied external force is suitable for enhancing the intensity of internal electric field of catalytic systems containing piezoelectric materials. [18,119] Tailoring microstructures to enlarge the specific surface area is usually applied to enlarge the scope of internal electric field, such as 0D, 1D, 2D, and 3D structures.…”
Section: Photocatalytic Pollutant Degradationmentioning
confidence: 99%
“…[26][27][28] Therefore, the creation and modulation of BIEF will greatly benefit for the efficient charge distribution and the substantial improvement in electro-catalytic performance. 29 During the past decades, research into the BIEF displays an increase in the exponential term in widespread applications and multicomponent devices and many effective strategies have been proposed for the modification of BIEF for further optimizing the catalytic performance of metalsupport catalysts. It was clearly found that some comprehensive reviews of BIEF in the field of photocatalysis have been well organized.…”
Section: Introductionmentioning
confidence: 99%